2014
DOI: 10.1016/j.exer.2013.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Müller glial dependent neuronal regeneration in the damaged adult zebrafish retina

Abstract: This article examines our current knowledge underlying the mechanisms involved in neuronal regeneration in the adult zebrafish retina. Zebrafish, which has the capacity to regenerate a wide variety of tissues and organs (including the fins, kidney, heart, brain, and spinal cord), has become the premier model system to study retinal regeneration due to the robustness and speed of the response and the variety of genetic tools that can be applied to study this question. It is now well documented that retinal dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
144
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(150 citation statements)
references
References 50 publications
5
144
0
1
Order By: Relevance
“…This finding is not surprising, because an ocular puncture wound is expected to disrupt the BRB, elicit an osmotic shock, and produce classic signaling cascades known to recruit immune cells to sites of traumatic injury. Importantly, this result highlights the potential for neutrophil involvement in retinal injury models that disrupt the BRB, e.g., light damage (7,63), puncture wounds (6), or toxin injection (31). Moreover, these data suggest that caution should be exercised when relating findings across regenerative paradigms involving different scales of injury, particularly with respect to immune system-related signaling cascades.…”
Section: Discussionmentioning
confidence: 98%
“…This finding is not surprising, because an ocular puncture wound is expected to disrupt the BRB, elicit an osmotic shock, and produce classic signaling cascades known to recruit immune cells to sites of traumatic injury. Importantly, this result highlights the potential for neutrophil involvement in retinal injury models that disrupt the BRB, e.g., light damage (7,63), puncture wounds (6), or toxin injection (31). Moreover, these data suggest that caution should be exercised when relating findings across regenerative paradigms involving different scales of injury, particularly with respect to immune system-related signaling cascades.…”
Section: Discussionmentioning
confidence: 98%
“…While these phenomena have been known for some time (Kirsche, 1950 and citations therein), we are now in a position to gain a deeper understanding of the cellular and molecular signaling pathways involved (recently reviewed in Berg et al, 2013;Gemberling et al, 2013;Goldman, 2014;Gorsuch and Hyde, 2014;Lenkowski and Raymond, 2014). Elucidating how this regeneration is accomplished at the cellular and molecular level may answer fundamental questions as to how stem/progenitor cells are directed to make new neurons, how this process is initiated and promoted, but also limited in space and time.…”
mentioning
confidence: 96%
“…In zebrafish, radial glial-like progenitors and the analogous Müller glia in the retina proliferate in response to injury and regenerate neurons and other cell types (Kroehne et al 2011;Kizil et al 2012;Gorsuch and Hyde 2013). Following spinal cord transection, the proliferative and neurogenic response of radial glia recapitulates many aspects of developmental neurogenesis (Reimer et al 2008(Reimer et al , 2009, and it has been suggested that this response of radial glia may partly occur in place of the contribution of astrocytes to the glial scar seen in mammals (Becker and Becker 2014).…”
Section: Fish Radial Glia and Their Relationship To Mammalian Astrocytesmentioning
confidence: 99%